Penerapan Massage Effleurage Menggunakan Virgin Coconut Oil Menurunkan Risiko Gangguan Integritas Kulit Pada Pasien Stroke Non Hemoragik - Angelica Tarigan; Rahayu Winarti (STIKES Columbia Asia Medan, 2025)
Background: Stroke is a medical condition characterized by a disruption in blood flow to the brain, most commonly resulting in ischemic stroke, which accounts for 70%–85% of all stroke cases. Prolonged immobility in stroke patients increases the risk of pressure ulcers. Effective prevention strategies Include regular repositioning and meticulous skin care. Effleurage massage, when combined with Virgin Coconut Oil (VCO), enhances blood circulation and skin hydration, thereby potentially reducing the risk of impaired skin integrity. Objective: To analyze the management of a non-hemorrhagic stroke patient Through the application of Effleurage Massage therapy using Virgin Coconut Oil (VCO) to reduce the risk of skin integrity impairment. Methods: This case study involved a non-hemorrhagic stroke patient who was observed during hospital visits over a three-day period. Effleurage massage using VCO was applied twice daily—once in the morning and once at night. Skin integrity was assessed before and after the intervention using the Braden Scale Results: A decrease in the risk of skin integrity impairment was observed following the intervention, as evidenced by improved Braden Scale scores. Conclusion: Effleurage Massage using Virgin Coconut Oil may serve as an effective complementary therapy to reduce the risk of skin integrity Impairment in non-hemorrhagic stroke patients.